2013
DOI: 10.1371/journal.pone.0083236
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Artery Perfusion with Anti-Tumor Necrosis Factor Alpha Antibody Reduces Cardiopulmonary Bypass-Induced Inflammatory Lung Injury in a Rabbit Model

Abstract: Inflammatory lung injury is one of the main complications associated with cardiopulmonary bypass (CPB). Tumor necrosis factor-α (TNF-α) is one of the key factors mediating the CPB-induced inflammatory reactions. Our previous studies have shown that endotracheal administration of anti-tumor necrosis factor-α antibody (TNF-α Ab) produces some beneficial effects on lung in a rabbit CPB model. In this study, we further examined the effects of pulmonary artery perfusion with TNF-α Ab (27 ng/kg) on lung tissue integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 20 publications
3
15
0
Order By: Relevance
“…[16][17][18] Indeed, a recent study has shown that CPB carried out in rabbits caused an increase in leakage of Evans blue dye administered intravenously, which could be inhibited by an antibody against tumor necrosis factor a. 19 Therefore, macrophage and neutrophils released during CPB could cause tumor necrosis factor a-induced apoptosis in pulmonary SMCs, such as that seen in this study.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…[16][17][18] Indeed, a recent study has shown that CPB carried out in rabbits caused an increase in leakage of Evans blue dye administered intravenously, which could be inhibited by an antibody against tumor necrosis factor a. 19 Therefore, macrophage and neutrophils released during CPB could cause tumor necrosis factor a-induced apoptosis in pulmonary SMCs, such as that seen in this study.…”
Section: Discussionsupporting
confidence: 49%
“…During CPB, there is minimal blood perfusion of pulmonary arteries/arteries and decreased oxygenation; these conditions are known to provoke an increased immunological response through ischemia–reperfusion injury and mechanical stress, causing atelectasis and lung dysfunction 16, 17, 18. Indeed, a recent study has shown that CPB carried out in rabbits caused an increase in leakage of Evans blue dye administered intravenously, which could be inhibited by an antibody against tumor necrosis factor α 19. Therefore, macrophage and neutrophils released during CPB could cause tumor necrosis factor α–induced apoptosis in pulmonary SMCs, such as that seen in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models of CPB in which the genetic background of the experimental animal is more uniform than in humans, including rabbit, piglet and rat models, it is consistently observed that the serum level of TNF-α is significantly increased during and following CPB (11,12,19,20). Notably, Qi et al (11) demonstrated that in a rabbit model of CPB, in addition to a significant increase of systemic levels of TNF-α, the serum level of TNF-α from the left atrium is significantly higher than that from the right atrium (Table I).…”
Section: Effects Of Cpb On Tnf-α Level In the Serum And Lung Tissuementioning
confidence: 99%
“…Dauber et al revealed that peak circulating TNF levels correlate with CPB-induced coronary and pulmonary vascular injury (21). Studies on a rabbit model of CPB demonstrated that endotracheal administration or pulmonary perfusion of a neutralizing antibody against TNF-α significantly reduced pulmonary edema and alleviated histological damage in the lung (11,12). In a rat model, TNF-α markedly induced pulmonary vascular barrier dysfunction with increased lung water content and impaired oxygenation (22).…”
Section: Effects Of Cpb On Tnf-α Level In the Serum And Lung Tissuementioning
confidence: 99%
See 1 more Smart Citation